Pembangunanisme dan teknokratisme: Konstruksi wacana media lokal terhadap pembangunan infrastruktur di Bandar Lampung - Prayoga, David; Khairullah; Nasution, Nadya Amalia (Program Studi Ilmu Komunikasi UII, 2025)
This study analyzes the discourse construction of the local Lampung media, Lampung Geh, in reporting the development of the cable car in Bandar Lampung during the period of February-June 2025. The study uses Teun A. van Dijk's critical discourse analysis model. This research examines four news articles focusing on text structure (macro, superstructure, micro), social cognition, and social context. The results show that the media consistently constructs the government as a visionary actor and foreign investors as saviors, while positioning the public passively. The study also reveals the dominant ideologies at work in the text: developmentalism, which naturalizes physical development as the sole indicator of progress while ignoring social and environmental factors, and technocratism, which depoliticizes development into technical-administrative issues, excluding public participation. Both of these ideologies work simultaneously to legitimize foreign capital involvement and to close off space for criticism of contract transparency, structural dependency risks, and locally based development alternatives. The media functions more as an instrument of political development legitimacy than as a critical public space. This research contributes to the study of development communication and promotes critical literacy among the public regarding local media discourse.